Effect of MT3 on Retinal and Choroidal TGF-β2 and HAS2 Expressions in Form Deprivation Myopia of Guinea Pig - Tao Li; Xiaodong Zhou; Bing Li; Bo Jiang (Journal of Ophthalmology)
Purpose. To confirm its dose-dependent effect on form deprivation myopia and evaluate the effect of MT3 at different tissue concentrations on changes in mRNA and protein expression for TGF-β2 and HAS2. Methods. MT3 was intravitreally injected into deprived eyes at two-day intervals. Refraction was measured by streak retinoscopy after cycloplegia. The axial dimensions were measured by A-scan ultrasound. The quantitative RT-PCR and Western blot were used to detect the changes of TGF-β2 and HAS2 expressions in the retina and choroid of guinea pigs. Results. MT3 treatment produced a significant dose-dependent reduction in relative myopia compared to FD group (both p<0.001). There were statistically significant increases in retinal and choroidal mRNA levels for both TGF-β2 and HAS2 after injections of 10 μM of MT3, when compared to the FD group. There were no significant differences in retinal and choroidal TGF-β2 protein expression levels between the MT3 treatment groups and FD group (all p>0.05). The injections of 10 μM of MT3 caused a marked decrease in retinal HAS2 protein expression level, when compared to the FD group (p=0.001). Conclusion. MT3 can inhibit form deprivation myopia, and MT3 treatment can result in changes of retinal and choroidal TGF-β2 and HAS2 mRNA and protein expressions.